Contemporary rehabilitation at cancer centres - Hojan, Katarzyna (Journal of Medical Science, 2014)
Aim. Cancer rehabilitation is an important, but often underutilized treatment in the comprehensive care of the cancer patient. The lack of appropriate referral by physicians unfamiliar with the concept of rehabilitation was identified as primary barriers to optimal delivery of rehabilitation care. Therefore, the aim of this paper is to describe the current situation in the world of science of cancer rehabilitation and to describe availability of professional resources in the selected countries in the world. Material and methods. This paper is a review article to describe rehabilitation models in cancer services for patients in selected cases in the world. Results. Rehabilitation should be applied in various settings, depending on the level of disability, extent of disease, medical acuity level of the patient, and available services. However, the rehabilitation systems in the world differ depending on the various social security and health-care systems, but they are largely based on a similar, multidimensional and multidisciplinary understanding of cancer rehabilitation. Conclusions. On the basis of description of the bio-psycho-social models, it can be seen that rehabilitation must be an integral and continuous part of all cancer care. There is strong evidence that rehabilitation is a well-tolerated and safe adjunct therapy that can mitigate several common treatment-related side effects among cancer patients.